Clifford's good deeds - Bridwell, Norman (New York : Four Winds Press, 1975)
Clifford, a very big dog who always overdoes his good deeds, finds something to do that is his size.
School Library Journal.
Library Journal.
Kirkus Review.
2.5
K-3
J
Keywords: Dogs -- Fiction; Clifford (Fictitious character : Bridwell) -- Fiction; Helping behavior -- Juvenile fiction